2020
DOI: 10.1038/s41431-020-00774-w
|View full text |Cite
|
Sign up to set email alerts
|

Copy neutral loss of heterozygosity (cnLOH) patterns in synchronous colorectal cancer

Abstract: Copy neutral loss of heterozygosity (cnLOH) is a common event in several human malignancies-positing this as a mechanism of carcinogenesis. However, the role of cnLOH in synchronous colorectal cancer (SCRC), a unique CRC subtype, is not well understood. The aim of this study was to establish a cnLOH profile of SCRC using a single-nucleotide polymorphism array (SNP-A), and to explore associations between cnLOH and the genomic landscape of frequently mutated genes in SCRC. Among 74 paired SCRC cases, the most fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The loss of one of these gene copies, termed as loss of heterozygosity (LOH), is one of the most common genetic alterations in cancer [1]. LOH has been playing a pivotal role in cancer development [2]. For instance, LOH was found to be involved in the relapse of acute lymphoblastic leukemia [3].…”
Section: To the Editormentioning
confidence: 99%
“…The loss of one of these gene copies, termed as loss of heterozygosity (LOH), is one of the most common genetic alterations in cancer [1]. LOH has been playing a pivotal role in cancer development [2]. For instance, LOH was found to be involved in the relapse of acute lymphoblastic leukemia [3].…”
Section: To the Editormentioning
confidence: 99%
“…the most frequent mutation cluster region was 16p11.2-p11.1 (59.5%), where CN-LOH was significantly associated with polyclonal synchronous colorectal cancers (p=0.038). 28 CN-LOH was also associated with the duplication of oncogenic mutations with concomitant loss of the normal allele in myeloid malignancies. 21 Therefore, combining mosaic mutations and genetic mutations is a more accurate way to achieve precise prediction of disease.…”
Section: Discussionmentioning
confidence: 99%
“…The establishment of LOH maps by cytogenetics [24] or, more recently, by genome-wide copy number analyses and genome sequencing, have enabled identification of chromosomal regions lost in different tumor types [25][26][27][28]. A study of~10 5 LOH events in 363 glioblastoma and 513 ovarian cancer samples revealed that LOH selectively occurs in early replicating regions, especially near RNA pol II-bound transcription start sites [29]. Together, these and other studies demonstrate that LOH in cancer genomes is not only affecting tumor suppressor genes but also numerous non-driver genes.…”
Section: Loh Leads To Loss Of Non-driver Genes and Endows Cancer Cells With Unique Vulnerabilitiesmentioning
confidence: 99%
“…In general, there are two types of LOH, (1) LOH with copy number losses (CNL-LOH), with a typical example of being losing the wildtype allele of a tumor suppressor, and (2) copy number neutral LOH (CNN-LOH), exemplified by the presence of two mutant alleles of WT1 (11p), FLT3 (13q), CEBPA (19q) and RUNX1 (21q) which resulted in a growth advantage in tumors, such as in leukemia [3]. A complete or partial deletion of a chromosome leads to CNL-LOH, while CNN-LOH is mainly caused by acquired uniparental disomy (UPD) and gene conversion, and occurs without net change in the copy number [4,5] (Figure 1). In principle, the presence of two mutant alleles generated by CNN-LOH could lead to an alteration at the gene expression level, however, it has been recently shown that there are allelic differences in gene expression [6], indicating that the exact expression level could be associated with specific gene expression patterns and regulated by other mechanisms.…”
Section: Introductionmentioning
confidence: 99%